PHYSICAL ACTIVITY GUIDELINES FOR CHILDREN - Fitria Dwi Andriyani (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2014)
AbstractMotor skill is a crucial element to be concerned since early childhood because it supports the children to pass throughtheir development tasks and helps the children in doing their daily activity. Children who have a high-level of motorskills tend to be more confidence and have more self-esteem when engaging with their friends. In contrast, childrenwho have a low-level of motor skills tend to have less confidence and self-esteem. This group of children could beexcluded when playing sport games because their friends assume that their involvement could disadvantage theteam. This situation could produce psychological effects to the children. Therefore, children should get supportsto develop their motor skills by doing many kinds of physical activities and sports. In addition, we need to considerabout the appropriate amounts and methods when giving children forms of physical activity. This article will describeabout proper physical activity guidelines for children, along with its benefit and type. This article also describes howto set the intensity for children in doing physical activity and how to promote physical activity for children, especiallyin the school setting. The objective is to provide knowledge to the community about the appropriate method of givingphysical activity for the children. The term of children cover 5 – 11 years old range.Keywords: guideline, physical activity, childrenAbstrakKeterampilan motorik adalah elemen yang krusial untuk diperhatikan sejak usia dini karena keterampilan tersebut akanmendukung anak dalam melewati tugas-tugas perkembangannya dan membantu anak dalam melakukan aktivitassehari-hari. Anak yang memiliki level tinggi keterampilan motorik cenderung lebih percaya diri dan memiliki harga dirilebih tinggi ketika bergaul dengan teman sebayanya. Secara kontras, anak yang memiliki level rendah keterampilanmotorik cenderung memiliki rasa percaya diri dan harga diri yang rendah. Kelompok anak berketerampilan motorikrendah ini dapat dihindari menjadi teman satu tim ketika bermain karena diasumsikan bahwa keterlibatan merekadalam permainan akan merugikan tim. Situasi ini dapat menimbulkan efek psikologis buruk bagi anak. Oleh karena itu,anak harus mendapat dukungan dalam mengembangkan keterampilan motoriknya dengan melakukan berbagai jenisaktivitas jasmani dan olahraga. Hal yang harus diperhatikan adalah dosis dan metode yang tepat dalam memberikananak bentuk-bentuk aktivitas jasmani. Artikel ini akan mendeskripsikan panduan aktivitas jasmani untuk anak, besertadengan keuntungan dan tipe-tipenya. Selain itu juga memberikan informasi mengenai cara menentukan intensitasanak dalam beraktivitas jasmani dan bagaimana cara mempromosikan aktivitas jasmani bagi anak, terutama dalamsetting sekolah. Tujuannya yaitu untuk menyediakan pengetahuan bagi masyarakat mengenai cara yang tepat dalammemberikan aktivitas jasmani untuk anak. Istilah anak dalam konteks ini adalah anak usia 5-11 tahun.Kata Kunci: panduan, aktivitas jasmani, anak